Analisis Struktur Biaya Dan Break Even Point Pada UMKM Salero Basamo - Rika Surianto Zalukhu; Rapat Piter Sony Hutauruk; Daniel Collyn; Yenni Mariani Sinurat; Murbanto Sinaga (Pusat Riset dan Inovasi Nasional, 2024)
Most micro, small, and medium-sized enterprises (MSMEs) have a limited understanding of sound business budget planning, which often leads to insufficiently prepared budget plans. However, effective budget planning can be achieved if MSMEs understand their cost structure and the break-even point of their business operations. Therefore, this study aims to analyze the cost structure and break-even point of Salero Basamo, an MSME located in Tebing Tinggi. The research adopts a qualitative descriptive approach, with data collection through interviews and observations, focusing on both production and non-production data. This data was then analyzed using cost structure analysis and break-even point analysis. The results indicate that Salero Basamo's cost structure is dominated by variable costs, accounting for 95.30% compared to 4.70% fixed costs. Furthermore, Salero Basamo reaches its break-even point when sales volume reaches 1,949 portions or sales revenue amounts to IDR 53,591,138. These findings have implications for the preparation of Salero Basamo's sales budget plan. To ensure profitability, Salero Basamo must set sales targets above 1,949 portions and revenue above IDR 53,591,138 in their budget plan. This study highlights that break-even point analysis can be a valuable tool for effective profit planning.